Bilingualism affects audiovisual phoneme identification - Burfin, Sabine; Pascalis, Olivier; Ruiz Tada, Elisa; Costa, Albert; Savariaux, Christophe; Kandel, Sonia (Frontiers in Psychology, 2014)
We all go through a process of perceptual narrowing for phoneme identification. As we become experts in the languages we hear in our environment we lose the ability to identify phonemes that do not exist in our native phonological inventory. This research examined how linguistic experience –i.e., the exposure to a double phonological code during childhood– affects the visual processes involved in non-native phoneme identification in audiovisual speech perception. We conducted a phoneme identification experiment with bilingual and monolingual adult participants. It was an ABX task involving a Bengali dental-retroflex contrast that does not exist in any of the participants’ languages. The phonemes were presented in audiovisual (AV) and audio-only (A) conditions. The results revealed that in the audio-only condition monolinguals and bilinguals had difficulties in discriminating the retroflex non-native phoneme. They were phonologically “deaf” and assimilated it to the dental phoneme that exists in their native languages. In the audiovisual presentation instead, both groups could overcome the phonological deafness for the retroflex non-native phoneme and identify both Bengali phonemes. However, monolinguals were more accurate and responded quicker than bilinguals. This suggests that bilinguals do not use the same processes as monolinguals to decode visual speech.